2019
DOI: 10.3390/fishes4010018
|View full text |Cite
|
Sign up to set email alerts
|

Chestnut Shell Extract Modulates Immune Parameters in the Rainbow Trout Oncorhynchus mykiss

Abstract: In this study, chestnut (Castanea sativa) shell was extracted with different solvents, and immunomodulatory activity was investigated in an in vitro model system using blood and intestinal leukocytes of Oncorhynchus mykiss. Gallic acid (GA) was used as a standard. Chestnut shell extract (CSE) and GA readily entered both blood and intestinal leukocytes. Superoxide anion production and phagocytosis were decreased by low doses of CSE and increased with high doses. CSE and GA differently regulated cytokine express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 79 publications
(99 reference statements)
1
9
0
Order By: Relevance
“…For instance, chlorogenic acid as a phenolic compound, which presented WLP as well as various medicinal herbs, could activate macrophages through calcineurin pathway in mice cell line (Wu et al, 2004). Additionally, in vitro study demonstrated that Gallic acid derived from Chestnut shell extract could stimulate blood leukocyte of O. mykiss (Coccia, Siano, Volpe, Varricchio, Eroldogan & Paolucci, 2019). Another in another in vitro study, dihydroquercetin as a flavonoid compound derived from deodar, demonstrated promoting effects on leukocyte to modulate phagocytic activity of Sparus aurata (Awad et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, chlorogenic acid as a phenolic compound, which presented WLP as well as various medicinal herbs, could activate macrophages through calcineurin pathway in mice cell line (Wu et al, 2004). Additionally, in vitro study demonstrated that Gallic acid derived from Chestnut shell extract could stimulate blood leukocyte of O. mykiss (Coccia, Siano, Volpe, Varricchio, Eroldogan & Paolucci, 2019). Another in another in vitro study, dihydroquercetin as a flavonoid compound derived from deodar, demonstrated promoting effects on leukocyte to modulate phagocytic activity of Sparus aurata (Awad et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Gallic acid is generally considered not dangerous, since it exerts a toxic effect only at high concentrations (Coccia, et al., 2019; Harishkumar et al., 2019; Singulani et al., 2017; Techer et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…One‐ring phenolic compounds, such as hydroxytyrosol and GA, are readily absorbed within 15 min from incubation in leukocyte cell culture (Coccia, et al., 2019) and intestinal epithelial transplants (Coccia, et al., 2019) of rainbow trout. In agreement with these findings, our exploratory experiments highlighted the rapid in vivo effect of GA occurring within the first 30 min of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, chestnut shell hydroalcoholic extracts tested on several human cell lines were suggested to display potential anti-angiogenic and anti-inflammatory effects [ 4 ]. When assayed on trout blood and intestinal leukocytes, they also elicited a stimulatory response of the immune system against possible infectious agents [ 5 ]. Several studies on rat models of diabetes fed with chestnut extracts demonstrated a diet-dependent increase of pancreatic cell viability [ 6 ] and a corresponding cytoprotective response against hepatorenal injury [ 7 ].…”
Section: Introductionmentioning
confidence: 99%